Processamento e caracterização da liga Al93Fe3Cr2Ti2 solidificada rapidamente - Bonavina, Luiz Fernando (2005)
The necessity to use materials presenting low density, high tensile strength and easy processing ability have led to the development of news materials and news processing techniques. More recently we can find in the literature, successful reports concerning the developing of bulk nanocrystalline composite alloys presenting a microstructure composed of Al + Quasicrystal + Al23Ti9 phases, obtained by extrusion of atomized powder. The goal of our work was to evaluate the perspective in obtaining bulk quasicrystalline composite, in centimeters scale, by spray deposition process. The Al93Fe3Cr2Ti2 alloy was processed by spray forming using nitrogen as atomizer gas onto a cooper substrate. To understand the influence of the cooling rate on the microstructure, the alloy was cast into an edge shaped cooper mould and the cooling rate has been estimated by using MAGMASOFT software. The samples were then characterized by the use of scanning (SEM) and transmission electron microscopy (TEM), X-ray diffraction (XRD), differential scanning calorimetry (DSC), Vickers microhardness measurements and also compressive tests at room temperature. The desired microstructure composed of quasicrystalline particles embedded in Al matrix has been formed only under the higher cooling rate: i) in 90µm thick region of the edge mould sample, where a cooling rate of 105 K/s has been estimated; ii) in the thinner (10mm) region of the spray formed deposit corresponding the peripherical area of the atomization cone. The results indicate that the spray forming is a promising process to produce bulk quasicrystalline composite alloys. However, to fully explore this potential the gas-metal ratio must be higher than that used in the present work, to maintain all the deposit at the same condition as observed at the peripherical region of the atomization cone.